Nilai-Nilai Prososial Dalam Kaulinan Oray-Orayan Di Sekolah Dasar Negeri Isola Kota Bandung - Tuti Istianti (Universitas PGRI Kanjuruhan Malang, 2018)
The verbal and gestures values disclosure of west java traditional play named â€œKaulinan Orayorayanâ€ is needed as a starting poin in improving learning at schools. The article explores and identifies the values of pro-social of the physical and phsychological activities of â€œKaulinan Oray-orayanâ€ in which etnopedagogically is rich of cultural and national values. Based on semiotics study and descriptive analysis, it is identified the pro-social values in â€œKaulinan Orayorayanâ€ such as getting fun, entertaining, helping, building friendship, sacrificing, generousity, and sharing. It is recommended that the valeus of â€œKaulinan Orayorayanâ€ should be applied and improved in the teaching and learning practices at schools.